A Review of Unmanned Aerial Vehicle (UAV) Applications In The Road Surveying - BIN MAHASSAN, SYAHMIN NASRULLAH; Sarif, Abd Sukor (Progress in Engineering Application and Technology, 2021)
Road transport is a must as it provides ample facilities benefits to a country and to individuals, especially in improving access to places jobs, economic resources, educational facilities, health centers and more. Behind the importance of transportation to the population, there is also a negative effect, namely, road accidents. The cause of an accident can be done by various factors. One of those factors is road design. This paper presents a review of recent developments in relation to the application of UAVs in three major domains of transportation, namely; road safety, traffic monitoring and highway infrastructure inspection. This study, includes data collection, data analysis, and results. Advance application of UAVs in extracting key information which will be utilized in accident investigation and assessment, traffic flow analysis and damage assessment roads. To further enhance the knowledge of the advantages of this UAV. In addition, the private sector especially needs to apply the use of this UAV for their company to increase the skilled manpower for the use of this UAV while accelerating all the processes that will be carried out especially in the surveying sector.